THE RELATIONSHIP BETWEEN TEACHER'S ATTENTION, LEARNING HABITS, AND HOME STUDY FACILITIES WITH MATHEMATICS LEARNING OUTCOMES - Novi Wahyu Nugroho; Harina Fitriyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Many factors influence the low mathematics learning outcome. Teachers' attention, learning habits, and home study facilities may affect students' mathematics learning outcomes. Therefore, this research was conducted in order to determine whether there is a positive and significant relationship between teacher's attention, learning habits, and home study facilities with mathematics learning outcomes in even semester of the eight-grade students at SMP Negeri 7 kebumen academic year of 2016/2017. The population in this research were all students of class VIII SMP Negeri 7 kebumen in academic year 2016/2017 consisting of 3 classes with a total of 92 students. Random sampling techniques used to get the class sample and collected VIII H as a sample that consists of 30 students. Data collection techniques were conducted by questionnaires to the teacher's attention, learning habits, and home study facilities. They are a test method for mathematics learning outcomes. Test instruments used validity and reliability. Prerequisite test analysis using normality test, independent, and linearity test. Hypothesis testing data analysis using simple linear regression analysis and multiple regression analysis and correlation. The results showed that there is a positive and significant correlation among teacher’s attention, learning habits and home study facilities with mathematics learning outcomes with Fcount = 11,97 and Ftable = 2,98 so Fcount > Ftable, multiple correlation coefficient (R) is 0,76, and the multiple determination coefficient (R2) is 0,58. While the multiple regression equation is , relatively contribution (X1) = 45,51%, the relative contribution (X2) = 31,19%, the relative contribution (X3) = 23,30% and effective contribution (X1) = 26,40%, the effective contribution (X2) = 18,10%, and the effective contribution (X3) = 13,52%.